2017
DOI: 10.15666/aeer/1502_159171
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Smart Green Building Architecture to Residential Project Based on Kaohsiung, Taiwan

Abstract: Abstract. In order to be in line with the thought of the general public with regard to the implementation of Green Architecture on Smart Residential Project, this study is based on the implementation of the Smart Green Architecture of congregate residual buildings in Kaohsiung as the main strategic promotion topic. In addition, this study realized the collection and consolidation of Smart Green Building promotion policy worldwide and carried out comparative analyses of both domestic and oversea Smart/green res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They preferred housings that are idyllic and are located in places that offer a high quality of living. Furthermore, Liu et al [38] administered a questionnaire to Kaohsiung residents and indicated that rigorous safety monitoring and holistic elderly care influenced consumers' purchases of high-quality housing, and these two factors are salient design concepts for age-friendly housing. They also found that age-friendly housing met the housing needs of females.…”
Section: Empirical Analysis Resultsmentioning
confidence: 99%
“…They preferred housings that are idyllic and are located in places that offer a high quality of living. Furthermore, Liu et al [38] administered a questionnaire to Kaohsiung residents and indicated that rigorous safety monitoring and holistic elderly care influenced consumers' purchases of high-quality housing, and these two factors are salient design concepts for age-friendly housing. They also found that age-friendly housing met the housing needs of females.…”
Section: Empirical Analysis Resultsmentioning
confidence: 99%
“…Hu et al suggested that performance considerations, such as health and comfort, are the key motivations for attracting consumers to purchase GHs [ 17 ]. Liu et al found in a survey conducted in Taiwan that a higher perception of the quality and economic characteristics of GHs may lead to a higher willingness to pay for residents [ 48 ]. Thus, if residents perceive higher functional benefits of GHs, then they will have a more positive overall perceived value of GHs.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…To cope with issues of global climate and environmental change, the ecocity concept has become an ideal goal in urban development in recent years [4]. Additionally, urban development-oriented ideas such as promoting alternative fuel vehicles, using solar energy equipment in residential situations, cultivating low-carbon living habits [5], providing environmental education [6,7], constructing green buildings [8,9], and implementing green community construction have been developed with the aim pf achieving the ideal goal of a low-carbon city [10,11].…”
Section: Introductionmentioning
confidence: 99%